Effects of Hydroxyurea Treatment on Haemolysis in Patients with Sickle Cell Disease at Muhimbili National Hospital, Tanzania - Gangji, Azra; Masamu, Upendo; Mgaya, Josephine; Ndunguru, Joyce; Jonathan, Agnes; Minja, Irene Kida; Makani, Julie; Balandya, Emmanuel; Ruggjao, Paschal; Nkya, Siana (Tanzania Journal of Science, 2021)
Tanzania is one of the countries with a high burden of sickle cell disease (SCD). Haemolytic anaemia is a clinical feature of SCD, and has been linked to major complications leading to morbidity and mortality. Treatment with hydroxyurea (HU) has shown to induce foetal haemoglobin (HbF) which in turn decreases haemolysis in patients. This study aimed to investigate the effects of HU on haemolysis in SCD patients attending Muhimbili National Hospital, Tanzania by comparing their haemolytic parameters before and after therapy. Patients meeting the criteria were initiated on HU therapy for 3 months. Two haemolytic biomarkers: unconjugated plasma bilirubin levels and absolute reticulocyte counts were measured from patients’ blood samples at baseline and after 3 months of HU therapy and compared. Both absolute reticulocyte counts and indirect plasma bilirubin levels significantly declined after HU therapy. Median (IQR) plasma unconjugated bilirubin levels dropped significantly from 20.3 (12.7–34.4) μmol/L to 14.5 (9.6–24.1) μmol/L (p < 0.001) and mean (SD) absolute reticulocyte counts dropped significantly from 0.29 (0.1) x 109/L to 0.17 (0.1) x 109/L (p < 0.001) after therapy, thus, a decline in both haemolytic biomarkers after treatment was observed. This study found a potential for use of HU therapy in managing SCD patients in our settings evidenced by improvements in their haemolytic parameters. Clinical trials with a lager sample size conducted for a longer time period would be beneficial in guiding towards the inclusion of HU in treatment protocols for the Tanzanian population. Keywords: Sickle cell disease, hydroxyurea, haemolysis, foetal haemoglobin.